Perencanaan Off Street Parking Pada RSUD Soewandhie - Joshua Leadika; Nugroho Utomo (LPPM Universitas Abdurrab, 2025)
RSUD Dr. Mohammad Soewandhi located in Simokerto Subdistrict Surabaya is a health service center that is visited by many visitors. The number of hospital visitors who are not followed by the availability of parking lots around the area causes many vehicles parked on the road on the access road to the hospital. So it is necessary to plan the parking area needs using off street parking to plan the probability of arrival and parking services for the next 5 years. From the calculation results obtained the distribution of motorcycles 1295 vehicles and cars 241 vehicles with an average parking time of 0.86 hours 2.46 hours. The highest probability value of motorcycle arrival pattern P(x) = 0.124127 and car P(x) = 0.27067. Obtained parking area for motorcycles 390 m2 and cars 1213 m2. There is an off street parking facility plan in the form of a parking building at Soewandhi Hospital with a parking supply of 389 SRP motorcycles and 55 SRP cars with a 5-year plan.